Market expansion and the scope of mass customization - Peter-J. Jost (Marketing Letters, 2023)
We consider a market in which two firms with their own customer base have the possibility to expand their business by customization to serve new customer segments. In a two-dimensional model, we examine the optimal scope of customization - that is, whether not to customize, to customize only one dimension, or to customize both dimensions - by analyzing the trade-off between market expansion and expected competition. Depending on the size of their own home markets, we show that in most market constellations one firm fully customizes its standard product whereas the other firm customizes maximally only one dimension. If price discrimination for customized products is possible, firms' incentives to customize increase. However, whereas customization under uniform pricing is always Pareto improving for both firms, it might be Pareto inferior under price discrimination. From a consumer perspective, the situation is reversed. Although full customization implies that customers' preferences are perfectly matched, they do not necessarily benefit from customization under uniform pricing, whereas price discrimination is always a Pareto improvement for customers.
Keywords: 380; Market expansion; Scope of customization; Limit pricing; Price discrimination